Routledge handbook of political Islam / edited by Shahram Akbarzadeh. - Akbarzadeh, Shahram (Routledge handbooks., 2023)
This updated edition covers a range of political actors that use Islam to advance their cause. Capturing this diversity, this volume also sheds light on some of the less-known experiences from South East Asia to North Africa.